The implementation of environmental management system in Kamunting Industrial Zone : a bio-economic approach / Huda Sameer Mohammed Rashad Almaarofi - Almaarofi, Huda Sameer Mohammed Rashad (2009)

(untitled)
Environmental Management Practices has become an important key factor in overall business planning and activities nowadays. Environmental Management System (EMS) is one of the environmental management practices which can assist organizations to meet their increasingly heavy onus of responsibility for better condition of future world’s environment. Moreover, firms that adopted EMS have expertise in a wide range of benefits such as: cost saving benefits and a clear reduction in environmental/natural liability and calamity. Many studies have been carried out on investigating the benefits of the EMS, particularly for economy; however, none of these studies had shown any relation to a biological economics’ model. In this study, Bio-Economic Models have been examined for 45 firms at Kamunting Industrial Zone/Malaysia. This study examined statistically the typical option of the environmental management aspect and showed the ability of EMS to decrease the cost of treatment effluent, decrease the capacity of treatment effluent, enhance the quality of water, and cost saving advantages in the area. The study indicated that 7% of the surveyed firms faced around 30%-40% cost benefit in their total operation cost in 2006. On the other hand, they were found to be more capable to reduce the capacity of the treatment pond, as well as improve the quality effluent. Arising from these findings, a true consideration should be given to maximize the adoption of the EMS and other environmental friendly practices, and minimize the consumption of natural resources in order to earn a healthy and better green world, both at present and in the future.